Escherichia coli grpE gene codes for heat shock protein B25.3, essential for both lambda DNA replication at all temperatures and host growth at high temperature. - Ang, D (1986)
We have identified the grpE gene product as the B25.3 heat shock protein of Escherichia coli on the following evidence: (i) a protein similar in size and isoelectric point to B25.3 was induced after infection of UV-irradiated bacteria by lambda grpE+ transducing phage, (ii) mutant phage lambda grpE40, isolated by its inability to propagate on grpE280 bacteria, failed to induce the synthesis of the B25.3 protein, and (iii) lambda grpE+ revertants, derived from phage grpE40 as able to propagate on grpE280 bacteria, simultaneously recovered the ability to induce synthesis of the B25.3 protein. In addition, we show that E. coli bacteria carrying the grpE280 mutation are temperature sensitive for bacterial growth at 43.5 degrees C. Through transductional analysis and temperature reversion experiments, it was demonstrated that the grpE280 mutation is responsible for both the inability of lambda to replicate at any temperature tested and the lack of colony formation at high temperature. At the nonpermissive temperature the rates of synthesis of DNA and RNA were reduced in grpE280 bacteria.